2015
DOI: 10.1016/j.irfa.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Economic consequences of key performance indicators' disclosure quality

Abstract: Starting from 2006, UK listed companies are required to analyse their performance by using Key Performance Indicators (KPIs) in specific sections of their annual reports and the UK Accounting Standard Board (ASB) provides companies with guidelines for the best practice regarding KPI disclosure. Motivated by the possible effects of the KPI disclosure quality, we examine their potential economic consequences for a sample of UK listed firms for the period 2006 to 2010. Our sample consists of 448 firm-year observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 55 publications
5
36
1
1
Order By: Relevance
“…Adjusted R Square: 0.678;F value: 6.651; The mixed results of this study are in line with Vafaei et al, (2011) who reports significant and insignificant association between disclosure and firm value in one study. These results confirm the findings of previous studies such as Uyar and Kilic (2012) and Elzahar et al, (2015) who claimed that the association between voluntary disclosure and firm value varies according to the proxy employed for the market value of the firm. Where, this study found in the first model based on the market based measure (MTBV) an insignificant correlation between firm value and the levels of voluntary risk disclosure.…”
Section: Fully Defines All the Variables Used ** Denote Correlation supporting
confidence: 91%
See 4 more Smart Citations
“…Adjusted R Square: 0.678;F value: 6.651; The mixed results of this study are in line with Vafaei et al, (2011) who reports significant and insignificant association between disclosure and firm value in one study. These results confirm the findings of previous studies such as Uyar and Kilic (2012) and Elzahar et al, (2015) who claimed that the association between voluntary disclosure and firm value varies according to the proxy employed for the market value of the firm. Where, this study found in the first model based on the market based measure (MTBV) an insignificant correlation between firm value and the levels of voluntary risk disclosure.…”
Section: Fully Defines All the Variables Used ** Denote Correlation supporting
confidence: 91%
“…Out of the many studies reported in the literature, only a few have explored firm value and disclosure in developed countries (Healy et al, 1999;Leuz and Verrecchia, 2000;Baek, Kang and Park, 2004;Da Silva and Alves, 2004;Uyar and Kilic, 2012;Elzahar et al, 2015) and only one study has examined firm value and disclosure in emerging economies . To the best of the researcher's knowledge, not a single study has explored the effect of voluntary risk disclosure on firm value and thus this is the first to do so.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations